Preparing Nurses for a Technology-Driven Future: A Recent Literature Review Based Study of Educational Needs and Strategies - Alqurashi, Hanan Awadh; Aotudi, Layla Mohammed Ismail; Hbtari, Salwa Ahmed Ibrahim; ALnoamiy, Hager Mohammed Ahmad; Falatah, Haneen Bakor Mohammed; Asiry, Maryam Ali; Gadi, Hassan Rayyani Ismail; Assiry, Abeer Muaidh Omar; Khatir, Firyal Yousef; Zain, Tahani Mostafa; Al Abdullah, Zainab Ali (Journal of Ecohumanism, 2024)
Background: The digital transformation of healthcare systems has redefined the role of nurses, demanding proficiency in technologies such as electronic health records, artificial intelligence, telehealth, and simulation-based learning. However, nursing education has not uniformly evolved to meet these emerging demands. Gaps in curriculum design, faculty preparedness, and infrastructure continue to hinder nurses' ability to provide safe and effective care in increasingly technology-driven environments.Aim: This systematic review aimed to examine the educational needs of nurses in relation to technological advancements and to identify evidence-based strategies to enhance digital readiness among nursing students and professionals.Method: A comprehensive literature search was conducted across five major databases—PubMed, CINAHL, Scopus, Web of Science, and ScienceDirect—for studies published between 2020 and 2024. Ten empirical studies meeting the inclusion criteria were selected following PRISMA guidelines. The selected studies were critically appraised for quality and synthesized thematically.Results: The analysis revealed four primary themes: digital competency gaps, faculty and institutional readiness, effectiveness of learning models, and learner perceptions. Studies consistently reported a misalignment between nursing curricula and technological expectations in clinical settings. Simulation-based learning and blended models showed positive outcomes, but their success was limited by inconsistent infrastructure and faculty support. Student confidence in digital tools was found to correlate strongly with training exposure.Conclusion: To prepare nurses for future healthcare environments, systemic reforms are essential. These include curriculum modernization, faculty development, infrastructure enhancement, and the integration of adaptive, technology-centered learning models. Such reforms are crucial to bridge the gap between nursing education and the digital future of healthcare.